It moves and decides many rotor unmanned aerial vehicle of rotational speed feather directly to drive formula oil - ZHANG ZHE; JIANG LINDI; CHEN HAO; WEI LIUFENG (2017)
The utility model provides an it moves and decides many rotor unmanned aerial vehicle of rotational speed feather directly to drive formula oil, including fuselage, driving system, undercarriage and avionics system, the fuselage the integrated fuselage of material is entirely answering, driving system constitute by engine system, feather system, oil feeding system and rotor system, the undercarriage be the skid landing gear, be provided with flexible hoist and mount position on it to link firmly different mission equipment. The utility model discloses need not drive mechanism, simple structure, weight alleviates 10%~20% relatively, the utility model discloses lean on the feather angle to adjust lift, little to the wearing and tearing of engine, the life -time dilatation is more than 30%, the fuselage adopts nested formula overall arrangement, the fuel feeding, supplies power, sprays etc. Inside the system all arranges the fuselage in, improves space utilization, reduces useless hindering. 本实用新型所采用的技术方案是种直驱式油动